Carbon-coated and silicon dioxide-embedded porous germanium high-performance germanium-based negative electrode material as well as preparation method and application thereof
Porous germanium is prepared by hydrogen thermal reduction method, and embedded silica microspheres and carbon coating modification are modified, which solves the problem of volume expansion of germanium anode material during circulation, and realizes the preparation of high-performance germanium-based anode material, which is suitable for lithium-ion battery anode materials.
Patent Information
- Application Number
- CN202510005738.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-01-03
AI Technical Summary
The volume expansion of the existing germanium negative electrode material during circulation leads to the powderization of the electrode material, which in turn leads to the failure of lithium-ion batteries. The production cost of nano-germanium is high and the process is complex, making it difficult to achieve commercial application.
Porous germanium was prepared by hydrogen thermal reduction method, and pores embedded in porous germanium were prepared by hydrolysis of tetraethyl orthosilicate. Finally, carbon coating modification was performed to prepare high-performance p-Ge/SiO2/C composite material.
This method realizes the preparation of high-performance germanium-based anode material with environmental protection, low pollution, high production efficiency, and has long cycle stability and excellent rate performance, and is suitable for lithium-ion battery anode material.
Smart Images

Figure CN119764421A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of negative electrode materials for lithium-ion batteries, and relates to a new method for preparing porous germanium by using a hydrogen thermal reduction method, and preparing silicon dioxide microspheres embedded in porous germanium by carbon coating and tetraethyl orthosilicate hydrolysis, and the high-performance germanium-based negative electrode material prepared therefrom, as well as the application of the high-performance lithium-ion battery negative electrode material. Background Art
[0002] Vigorously developing new energy electric vehicles has become a national strategic plan. In order to make pure electric vehicles become mainstream, it is necessary to break through the key core technology of new energy vehicles - high energy density power lithium-ion batteries. With the breakthrough in the research of ternary positive electrode materials, higher requirements are also put forward for the performance of negative electrode materials. Although the theoretical specific capacity of germanium (1600mAh g -1 ) is only half of that of silicon, and germanium is more expensive than silicon, but germanium has a smaller volume change during the electrochemical cycle, the ion diffusion rate of germanium is 400 times higher than that of silicon, and the electronic conductivity is 4 orders of magnitude higher than that of silicon. The density of germanium is more than twice that of silicon (Ge is 5.3g cm -3 ; Si is 2.33 g cm -3 ), so it can store more charge per volume than silicon and has broader application prospects. However, the non-negligible volume expansion of germanium during the cycle (about 230%) will cause the electrode material to pulverize and further cause battery failure. Therefore, there are still many problems to realize the commercial application of germanium negative electrode materials. At present, research on germanium negative electrodes mainly focuses on alleviating the volume effect of germanium through carbon coating modification and improving the ionic and electronic conductivity of the material. In addition, reducing the size of Ge particles to the nanoscale can reduce the mechanical stress generated during the cycle and thus improve the cycle performance. However, nano-germanium will result in a low initial coulomb efficiency (ICE) of the electrode material, poor tap density and volumetric performance, high production costs, and complex processes.
[0003] Zhang et al. utilized the strong binding interaction between Ge and ZnS to form ZnS coated with polydopamine. 2 GeO 4After two-step carbonization and sulfurization of the nanorod precursor, the dispersed Ge nanoparticles were successfully encapsulated in a thin ZnS protective shell and a nitrogen-doped carbon layer. The synthesized Ge-ZnS@NC anode exhibited stable long-cycle performance and excellent rate performance, but the above-mentioned synthesis method is complicated and has low production efficiency, making it difficult to achieve large-scale production (Zhonghua Zhang, Lingjie Li, Jing Liu, Xiaosong Guo, Kun Chao, Changming Mao, Guicun Li, Alleviated volume changes of germanium anode via facile chemical confinement strategy, Chemical Engineering Journal, 497, 2024, 154741).
[0004] Yan et al. studied the morphology and lithium storage performance of nanoporous Ge (np-Ge), silver nanoparticles embedded in nanoporous Ge (Ag / np-Ge), and Ge nanoparticles embedded in nanoporous Ag (Ge / np-Ag). The results show that when a high proportion of Ge is used as the main active material, a higher theoretical capacity can be guaranteed, and the porous network structure can provide sufficient space for the volume expansion and contraction of the material. In addition, the embedded Ag nanoparticles can promote the electron transfer rate. The results show that the Ag / np-Ge electrode has the best cycling stability. However, the above preparation method involves high costs and is difficult to achieve commercial application (Yonghui Yan, Yang Liu, Yongguang Zhang, Chunling Qin, Zhumabay Bakenov, Zhifeng Wang, Improving the cycling stability of three-dimensional nanoporous Ge anode by embedding Ag nanoparticles for high-performance lithium-ion battery, Journal of Colloid and Interface Science, 592, 2021, 103-115). Therefore, how to improve the application of germanium materials in lithium-ion battery negative electrode materials in a more economical, environmentally friendly and effective manner is still a difficult problem that needs further research and development in this field. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a new high-performance germanium-based negative electrode material p-Ge / SiO2 with controllable low pollution and high production efficiency and carbon coating and silicon dioxide embedded in porous germanium.2 / C composite material and its preparation method and application. The method is characterized in that the inert SiO2 is prepared by hydrolyzing tetraethyl orthosilicate. 2 The microspheres, as pore fillers of porous germanium, have a pinning effect on the volume change of porous germanium during the charge and discharge cycle, limiting the volume change of germanium during subsequent cycles, and further coating with a carbon coating to obtain high-performance p-Ge / SiO 2 / C composite material.
[0006] The technical solution of the present invention is described in detail below.
[0007] The present invention provides a method for preparing a high-performance germanium-based negative electrode material with carbon coating and silicon dioxide embedded in porous germanium. The method uses hydrogen as a thermal reaction source to reduce germanium dioxide powder into porous germanium (p-Ge), then hydrolyzes tetraethyl orthosilicate under alkaline conditions to prepare silicon dioxide microspheres and embeds them into the pores of p-Ge, and finally mixes with carbon material and carbonizes at high temperature to achieve carbon coating modification, thereby preparing p-Ge / SiO2 with long cycle stability and excellent rate performance. 2 / C composite material. The specific preparation method includes the following steps:
[0008] S1, subjecting germanium dioxide powder to a low-temperature thermal reduction reaction in a hydrogen atmosphere to obtain a porous germanium material p-Ge material;
[0009] S2, adding p-Ge to a mixed solution of anhydrous ethanol and deionized water, then adding a surfactant and tetraethyl orthosilicate and stirring evenly, and reacting under alkaline conditions;
[0010] S3, carbon coating the above reaction product to obtain p-Ge / SiO 2 / C composite material.
[0011] Preferably, the particle size of the germanium dioxide powder in step S1 is 3 to 30 microns.
[0012] Preferably, in step S1, a layer of germanium dioxide powder is spread in the alumina porcelain boat for thermal reduction reaction, and more preferably the thickness of the spread is 2 mm. More preferably, the flow rate of the hydrogen atmosphere should be maintained at 50 to 200 ml / min. More preferably, the hydrogen atmosphere is high-purity hydrogen.
[0013] Preferably, the thermal reduction condition in step S1 is thermal reduction at 400°C for more than 8 hours, more preferably 8 to 14 hours. If the temperature is too low, the reduction reaction is difficult to achieve. If the temperature is too high, the pores of the porous germanium will grow and close during the high-temperature reduction process, resulting in a decrease in the corresponding electrochemical performance, and higher temperature conditions will also increase energy consumption.
[0014] Preferably, the volume ratio of deionized water and anhydrous ethanol in the mixed solution in step S2 should be 1: (1-5). By adopting a solvent system of anhydrous ethanol and water, ethanol can act as a solvent in the reaction, improve the solubility of tetraethyl silicate, ensure that the reactants can fully contact and react evenly, and avoid the uneven reaction that may be caused by directly using water as a reaction medium, thereby affecting the quality and yield of silicon dioxide. At the same time, the addition of ethanol can also effectively control the reaction rate, avoid the reaction of tetraethyl silicate with water may be too violent, resulting in uneven particle size of silicon dioxide, and may even generate a large amount of heat and gas, posing a safety hazard.
[0015] Preferably, in step S2, after p-Ge is added to the solvent, ultrasonic stirring is performed to uniformly mix the p-Ge, and more preferably, the ultrasonic power is 200 W and the ultrasonic time is 30 to 60 min.
[0016] Preferably, the surfactant in step S2 is hexadecyltrimethylammonium bromide.
[0017] Preferably, the mass ratio of p-Ge to surfactant added in step S2 should be 20:(0.1-2).
[0018] Preferably, the volume ratio of deionized water and tetraethyl orthosilicate added in step S2 should be 20:(0.1-2). Under this condition, the hydrolysis rate of tetraethyl orthosilicate is more suitable.
[0019] Preferably, the feeding amount of p-Ge and tetraethyl orthosilicate in step S2 is 0.2 g: 0.25-1 mL.
[0020] Preferably, the alkaline condition in step S2 is a pH not less than 8, and the reaction time is not less than 18 hours. More preferably, ammonia water or conventional alkaline solution such as sodium hydroxide or potassium hydroxide is added dropwise to make the pH of the mixed solution system 8-10, and stirred for 24 hours.
[0021] Preferably, after the reaction in step S2 is completed, the reaction product is successively washed by centrifugation with deionized water and anhydrous ethanol and dried to collect the reaction product; more preferably, the reaction product is washed by centrifugation with deionized water and anhydrous ethanol at a speed of 6000 rpm for 5 times each and dried at 80°C for 12 hours.
[0022] Preferably, the carbon coating step in step S3 is specifically as follows: stirring the reaction product and the carbon material and ultrasonically dispersing them in deionized water, evaporating the water in the suspension, and then calcining for 2 hours in an inert atmosphere at 600-900°C; the carbon coating conditions of the present invention have the advantages of low cost, simple synthesis, and easy implementation.
[0023] More preferably, the carbon material is one or a combination of sucrose, glucose, chitosan, citric acid and cellulose;
[0024] More preferably, the water is removed by evaporating the suspension at a temperature above 100°C for at least 1 hour, and more preferably, the water is removed by evaporating the suspension at a temperature between 120°C and 180°C for 2 hours;
[0025] More preferably, calcined at 700° C. in an inert atmosphere for 2 h;
[0026] More preferably, the inert atmosphere is at least one of nitrogen, helium and argon.
[0027] The present invention also provides a high-performance germanium-based negative electrode material p-Ge / SiO2 prepared by any of the above preparation methods, which is carbon-coated and silicon dioxide-embedded porous germanium. 2 / C composite material.
[0028] The present invention also provides a high-performance germanium-based negative electrode material p-Ge / SiO2 coated with carbon and embedded with silicon dioxide in porous germanium. 2 Application of / C composite materials as negative electrode materials for lithium-ion batteries.
[0029] The present invention provides a new method for preparing a high-performance germanium-based negative electrode material. First, porous germanium (p-Ge) is prepared by thermally reducing germanium dioxide with low-temperature hydrogen, then silicon dioxide microspheres are prepared by hydrolyzing tetraethyl orthosilicate and embedded in the pores of p-Ge, and finally modified by carbon coating. The preparation process of the present invention is environmentally friendly and low-pollution, has high production efficiency, and a controllable synthesis process without introducing by-products or side reactions. The porous germanium pore filling rate can be controlled by adjusting the amount of raw materials, and the synthesis of different products is achieved. The prepared p-Ge / SiO 2 / C composites have excellent cycle stability and rate performance.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] (1) The present invention provides an environmentally friendly, low-pollution, simple and controllable reaction, high production efficiency, no solid phase by-product generation, and efficient synthesis of p-Ge / SiO 2 A new approach to C / C composites.
[0032] (2) The high-performance germanium-based negative electrode material p-Ge / SiO provided by the present invention 2 As a negative electrode material for lithium-ion batteries, the C / C composite material has the characteristics of good conductivity, good cycle stability and excellent rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 p-Ge, p-Ge / C, p-Ge / SiO prepared by implementing 1, 2, 3, 4, 5 and 6 of the present invention 2 and p-Ge / SiO2 XRD patterns of / C composites;
[0034] Figure 2 p-Ge, p-Ge / C, p-Ge / SiO prepared by implementing 1, 2, 3, 4, 5 and 6 of the present invention 2 and p-Ge / SiO 2 Scanning electron microscope (SEM) images of the / C composites;
[0035] Figure 3 p-Ge, p-Ge / C, p-Ge / SiO prepared by implementing 1, 2, 3, 4, 5 and 6 of the present invention 2 and p-Ge / SiO 2 / C composites at 0.5Ag -1 Cycling performance diagram under current density;
[0036] Figure 4 p-Ge, p-Ge / C, p-Ge / SiO prepared by implementing 1, 2, 3, 4, 5 and 6 of the present invention 2 and p-Ge / SiO 2 / C composites at 1.0Ag -1 Cycling performance diagram under current density;
[0037] Figure 5 p-Ge, p-Ge / C, p-Ge / SiO prepared by implementing 1, 2, 3, 4, 5 and 6 of the present invention 2 and p-Ge / SiO 2 / C composite material rate performance diagram at different current densities;
[0038] Figure 6 p-Ge, p-Ge / C, p-Ge / SiO prepared by implementing 1, 2, 3, 4, 5 and 6 of the present invention 2 and p-Ge / SiO 2 EIS graph of the / C composite material. DETAILED DESCRIPTION
[0039] In order to better clarify and understand the purpose, process scheme and advantages of the present invention, the technical scheme and implementation method of the present invention are further described clearly, completely and in detail through specific examples and in combination with the accompanying drawings. It should be noted that the embodiments described in the present invention are implemented on the premise of the technical scheme of the present invention, and detailed implementation methods and specific operating processes are given, but they are only part of the embodiments of the present invention, not all of the embodiments. The specific implementation methods described are limited to explaining and interpreting the present invention, and do not limit the present invention. Based on the embodiments in the present invention, all other implementation methods obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0040] The experimental methods and conditions used in the embodiments of the present invention are conventional methods and conventional conditions unless otherwise specified. The materials, reagents or instruments used in the embodiments, unless otherwise specified, can be obtained from commercial sources or prepared by conventional methods. The reaction conditions embodied in the content of the invention of the present invention can achieve the reaction and obtain the product of the expected effect. Due to space limitations, some embodiments are listed below to further illustrate the advantages of the technical solution of the present invention.
[0041] Embodiment 1:
[0042] Step 1: Preparation of p-Ge material
[0043] S1. Spread a 2 mm thick layer of germanium dioxide powder in an alumina porcelain boat and place it in a tube furnace. Heat reduce it at 400°C for 10 hours at a high purity hydrogen flow rate of 100 ml / min. After cooling in the furnace, a porous p-Ge material can be obtained. The particle size and pore size data are shown in Table 1, and the element percentage is shown in Table 2.
[0044] Figure 1 This is the XRD diffraction pattern of p-Ge material. Compared with the standard PDF card 04-0545, only the characteristic diffraction peak of Ge exists.
[0045] Figure 2 This is the SEM image of the p-Ge material. As can be seen from the figure, it is a porous honeycomb structure.
[0046] Step 2: Preparation of button lithium-ion battery
[0047] The active material (p-Ge material), SuperP and polyacrylic acid (PAA) were dissolved in deionized water at a mass ratio of 6:2:2 and then evenly coated on copper foil (coating amount was 0.8 g), dried in a vacuum oven at 120°C for 12 hours, and then pressed with a roller press. The electrode sheet was cut into a 12 mm diameter disc using a slicer to obtain the electrode disc for testing. The CR2032 button half-cell was assembled in an argon-filled glove box, with a lithium sheet as the counter electrode, a Cellgard 2500 film as the separator, and an electrolyte consisting of 1M LiPF 6 It is mixed in EC / DEC / EMC (1:1:1, vol%) with 5 vol% FEC and 1 vol% VC.
[0048] Figure 3 The button-type lithium-ion battery assembled for this embodiment is 0.5Ag -1 Cyclic performance diagram in the current density and voltage range of 0.01 to 2.0 V. The capacity of the p-Ge material dropped sharply after 150 charge and discharge cycles, and the final discharge capacity was only 405 mAh g -1 , the capacity retention rate is only 25.5% (compared with the 4th cycle), and the cycle stability is poor.
[0049] Figure 4 The button-type lithium-ion battery assembled for this embodiment is 1.0Ag -1 Cyclic performance diagram in the current density and voltage range of 0.01 to 2.0 V. The capacity of the material dropped sharply after 150 charge and discharge cycles, and the final discharge capacity was only 438 mAh g -1 , the capacity retention rate is only 27.5% (compared with the 4th cycle), and the cycle stability under high current is poor.
[0050] Figure 5 This is the rate performance diagram of the button-type lithium-ion battery assembled in this embodiment at different current densities. It can be seen from the figure that after the material is cycled at different current densities, when the current density is finally maintained at 1.0Ag -1 After 120 cycles, the final discharge capacity is only 386 mAh g -1 , the capacity retention rate is only 25.9% (compared with the 31st cycle), showing poor rate performance.
[0051] Figure 6 The electrochemical impedance spectroscopy (EIS) of the button-type lithium-ion battery assembled in this embodiment was tested in the range of 1 MHz to 0.1 Hz. The charge transfer impedance (Rct value) of the material was about 33Ω.
[0052] Embodiment 2:
[0053] Step 1: Preparation of p-Ge / SiO2 -0.25 Composite Material
[0054] S1. The preparation method is consistent with that in Example 1: a layer of 2 mm thick germanium dioxide powder is spread in an alumina porcelain boat and placed in a tube furnace. The alumina porcelain boat is subjected to thermal reduction at 400° C. for 10 h at a high-purity hydrogen flow rate of 100 ml / min. The porous p-Ge material is obtained after cooling in the furnace.
[0055] S2, add 0.2g of p-Ge to a mixed solution of 80ml of anhydrous ethanol and 20ml of deionized water, stir and ultrasonicate at an ultrasonic power of 200W for 1h to make the mixed solution uniform. Then add 0.02g of hexadecyltrimethylammonium bromide and 0.25ml of tetraethyl orthosilicate, stir for 30min to make it uniform;
[0056] S3, add 2 ml of ammonia water to the above mixed solution until pH = 9 to trigger the hydrolysis of tetraethyl orthosilicate, and stir for 24 hours. After the hydrolysis reaction is completed, centrifuge and wash at 6000 rpm for 5 times each with deionized water and anhydrous ethanol, and dry at 80 ° C for 12 hours to finally obtain p-Ge / SiO 2 -0.25 composite material. The particle size and pore size data are shown in Table 1, and the element percentages are shown in Table 2.
[0057] Figure 1 p-Ge / SiO 2 -0.25 XRD diffraction pattern of the composite material. Compared with the standard PDF card 04-0545, only the characteristic diffraction peak of Ge exists. 2 -0.25 composite material SiO near 22° 2 The broad peak is not obvious, this is because SiO 2 The filling amount is low.
[0058] Figure 2 p-Ge / SiO 2 -0.25 composite material SEM image. As can be seen from the figure, p-Ge / SiO 2 -0.25 The composite material presents a porous honeycomb structure similar to that of the p-Ge material, with the pores being only slightly filled.
[0059] Step 2: Preparation of button lithium-ion battery
[0060] The battery preparation method is the same as that in Example 1, except that the active material is different: the active material (p-Ge / SiO 2-0.25 composite material), Super P and polyacrylic acid (PAA) were dissolved in deionized water at a mass ratio of 6:2:2 and then evenly coated on copper foil (coating amount was 0.8g), dried in a vacuum oven at 120℃ for 12h, and then pressed with a roller press. The electrode sheet was cut into a disc with a diameter of 12mm using a slicer to obtain the electrode disc for testing. The CR2032 button half-cell was assembled in an argon-filled glove box, with a lithium sheet as the counter electrode, a Cellgard 2500 film as the separator, and an electrolyte consisting of 1MLiPF 6 It is mixed in EC / DEC / EMC (1:1:1, vol%) with 5 vol% FEC and 1 vol% VC.
[0061] Figure 3 The button-type lithium-ion battery assembled for this embodiment is 0.5Ag -1 Cycling performance diagram in the current density and voltage range of 0.01 to 2.0 V. p-Ge / SiO 2 The capacity of the -0.25 composite material dropped sharply after 150 charge and discharge cycles, and the final discharge capacity remained 542 mAh g -1 The capacity retention rate is 47.2% (compared with the 4th cycle), and the cycle stability is poor.
[0062] Figure 4 The button-type lithium-ion battery assembled for this embodiment is 1.0Ag -1 Cyclic performance diagram in the current density and voltage range of 0.01 to 2.0 V. The capacity of the material dropped sharply after 150 charge and discharge cycles, and the final discharge capacity was only 332 mAh g -1 , the capacity retention rate is only 27.5% (compared with the 4th cycle), and the cycle stability under high current is poor.
[0063] Figure 5 This is the rate performance diagram of the button-type lithium-ion battery assembled in this embodiment at different current densities. It can be seen from the figure that after the material is cycled at different current densities, when the current density is finally maintained at 1.0Ag -1 After 120 cycles, the final discharge capacity is only 319 mAh g -1 , the capacity retention rate is only 28.1% (compared with the 31st cycle), showing poor rate performance.
[0064] Figure 6 The electrochemical impedance spectroscopy (EIS) of the button-type lithium-ion battery assembled in this embodiment was tested in the range of 1 MHz to 0.1 Hz. The charge transfer impedance (Rct value) of the material was about 33Ω.
[0065] Embodiment 3:
[0066] Step 1: Preparation of p-Ge / SiO 2 -0.5 composite material (the amount of tetraethyl orthosilicate added was changed based on Example 2)
[0067] S1. Spread a 2 mm thick layer of germanium dioxide powder in an alumina porcelain boat and place it in a tube furnace. Heat reduce it at 400°C for 10 h at a high purity hydrogen flow rate of 100 ml / min. After cooling in the furnace, a porous p-Ge material can be obtained.
[0068] S2, add 0.2g of p-Ge to a mixed solution of 80ml of anhydrous ethanol and 20ml of deionized water, stir and ultrasonicate at an ultrasonic power of 200W for 1h to make the mixed solution uniform. Then add 0.02g of hexadecyltrimethylammonium bromide and 0.5ml of tetraethyl orthosilicate, stir for 30min to make it uniform;
[0069] S3, add 2 ml of ammonia water to the above mixed solution until pH = 9 to trigger the hydrolysis of tetraethyl orthosilicate, and stir for 24 hours. After the hydrolysis reaction is completed, centrifuge and wash at 6000 rpm for 5 times each with deionized water and anhydrous ethanol, and dry at 80 ° C for 12 hours to finally obtain p-Ge / SiO 2 -0.5 composite material. The particle size and pore size data are shown in Table 1, and the element percentages are shown in Table 2.
[0070] Figure 1 p-Ge / SiO 2 -0.5 XRD diffraction pattern of the composite material. Compared with the standard PDF card 04-0545, only the characteristic diffraction peak of Ge exists. 2 -0.5 composite material SiO near 22° 2 The broad peak is not obvious, this is because SiO 2 The filling amount is not high.
[0071] Figure 2 p-Ge / SiO 2 -0.5 composite material SEM image. As can be seen from the figure, p-Ge / SiO 2 The -0.5 composite material exhibits a porous honeycomb structure similar to that of the p-Ge material, but the holes are partially filled.
[0072] Step 2: Preparation of button lithium-ion battery
[0073] The battery preparation method is the same as that in Example 1, except that the active material is different: the active material (p-Ge / SiO 2-0.5 composite material), SuperP and polyacrylic acid (PAA) were dissolved in deionized water at a mass ratio of 6:2:2 and then evenly coated on copper foil (coating amount was 0.8g), dried in a vacuum oven at 120℃ for 12h, and then pressed with a roller press. The electrode sheet was cut into a disc with a diameter of 12mm using a slicer to obtain the electrode disc for testing. The CR2032 button half-cell was assembled in an argon-filled glove box, with a lithium sheet as the counter electrode, a Cellgard 2500 film as the separator, and an electrolyte consisting of 1MLiPF 6 It is mixed in EC / DEC / EMC (1:1:1, vol%) with 5 vol% FEC and 1 vol% VC.
[0074] Figure 3 The button-type lithium-ion battery assembled for this embodiment is 0.5Ag -1 Cycling performance diagram in the current density and voltage range of 0.01 to 2.0 V. p-Ge / SiO 2 -0.5 The composite material has a final discharge capacity of 659 mAh g after 150 charge and discharge cycles. -1 , the capacity retention rate is as high as 80.7% (compared with the 4th cycle), but the final remaining specific capacity is not high.
[0075] Figure 4 The button-type lithium-ion battery assembled for this embodiment is 1.0Ag -1 The current density and cycle performance in the voltage range of 0.01 to 2.0 V. The final discharge capacity of the material after 150 charge and discharge cycles is 552 mAh g -1 , the capacity retention rate is 68.0% (compared with the 4th cycle), but the final remaining specific capacity is still not high.
[0076] Figure 5 This is the rate performance diagram of the button-type lithium-ion battery assembled in this embodiment at different current densities. It can be seen from the figure that after the material is cycled at different current densities, when the current density is finally maintained at 1.0Ag -1 After 120 cycles, the final discharge capacity is 611 mAh g -1 ,The capacity retention rate is as high as 85.1% (compared with the 31st cycle), showing good rate performance, but the final residual specific capacity is not high.
[0077] Figure 6 The electrochemical impedance spectroscopy (EIS) of the button-type lithium-ion battery assembled in this embodiment was tested in the range of 1 MHz to 0.1 Hz. The charge transfer impedance (Rct value) of the material was about 36Ω.
[0078] Embodiment 4:
[0079] Step 1: Preparation of p-Ge / SiO 2 -1 Composite material (the amount of tetraethyl orthosilicate added was changed based on Example 2)
[0080] S1. Spread a 2 mm thick layer of germanium dioxide powder in an alumina porcelain boat and place it in a tube furnace. Heat reduce it at 400°C for 10 h at a high purity hydrogen flow rate of 100 ml / min. After cooling in the furnace, a porous p-Ge material can be obtained.
[0081] S2, add 0.2g of p-Ge to a mixed solution of 80ml of anhydrous ethanol and 20ml of deionized water, stir and ultrasonicate at an ultrasonic power of 200W for 1h to make the mixed solution uniform. Then add 0.02g of hexadecyltrimethylammonium bromide and 1ml of tetraethyl orthosilicate, stir for 30min to make it uniform;
[0082] S3, add 2 ml of ammonia water to the above mixed solution until pH = 9 to trigger the hydrolysis of tetraethyl orthosilicate, and stir for 24 hours. After the hydrolysis reaction is completed, centrifuge and wash at 6000 rpm for 5 times each with deionized water and anhydrous ethanol, and dry at 80 ° C for 12 hours to finally obtain p-Ge / SiO 2 -0.5 composite material. The particle size and pore size data are shown in Table 1, and the element percentages are shown in Table 2.
[0083] Figure 1 p-Ge / SiO 2 -1 composite material XRD diffraction pattern. Compared with the standard PDF card 04-0545, the characteristic diffraction peak of Ge appears, and an obvious broad peak appears near 22°, which is amorphous SiO 2 .
[0084] Figure 2 p-Ge / SiO 2 -1 composite material SEM image. As can be seen from the figure, p-Ge / SiO 2 -1 The pore structure of the composite material has almost disappeared, and the outer surface has exposed obvious SiO 2 Microspheres.
[0085] Step 2: Preparation of button lithium-ion battery
[0086] The battery preparation method is the same as that in Example 1, except that the active material is different: the active material (p-Ge / SiO 2-1 composite material), SuperP and polyacrylic acid (PAA) were dissolved in deionized water at a mass ratio of 6:2:2 and then uniformly coated on copper foil (coating amount was 0.8 g), dried in a vacuum oven at 120°C for 12 h, and then pressed with a roller press. The electrode sheet was cut into discs with a diameter of 12 mm using a slicer to obtain the electrode discs for testing. The CR2032 button half-cell was assembled in an argon-filled glove box, with a lithium sheet as the counter electrode, a Cellgard 2500 film as the separator, and an electrolyte consisting of 1M LiPF 6 It is mixed in EC / DEC / EMC (1:1:1, vol%) with 5 vol% FEC and 1 vol% VC.
[0087] Figure 3 The button-type lithium-ion battery assembled for this embodiment is 0.5Ag -1 Cycling performance diagram in the current density and voltage range of 0.01 to 2.0 V. p-Ge / SiO 2 -1 The composite material has a final discharge capacity of 558 mAhg after 150 charge and discharge cycles. -1 , the capacity retention rate is as high as 95.7% (compared with the 4th cycle), but the final residual specific capacity is low, which is difficult to meet the high capacity requirements of commercialization.
[0088] Figure 4 The button-type lithium-ion battery assembled for this embodiment is 1.0Ag -1 The current density and cycle performance in the voltage range of 0.01 to 2.0 V. The final discharge capacity of the material after 150 charge and discharge cycles is 484 mAh g -1 , the capacity retention rate is 85.4% (compared with the 4th cycle), but the final remaining specific capacity is still not high.
[0089] Figure 5 This is the rate performance diagram of the button-type lithium-ion battery assembled in this embodiment at different current densities. It can be seen from the figure that after the material is cycled at different current densities, when the current density is finally maintained at 1.0Ag -1 After 120 cycles, the final discharge capacity is 518 mAh g -1 ,The capacity retention rate is as high as 93.8% (compared with the 31st cycle), showing good rate performance, but the final residual specific capacity is still not high.
[0090] Figure 6 The electrochemical impedance spectroscopy (EIS) of the button-type lithium-ion battery assembled in this embodiment was tested in the range of 1 MHz to 0.1 Hz. The charge transfer impedance (Rct value) of the material was about 36Ω.
[0091] Embodiment 5:
[0092] Step 1: Preparation of p-Ge / SiO 2 / C Composite Materials
[0093] S1. Spread a 2 mm thick layer of germanium dioxide powder in an alumina porcelain boat and place it in a tube furnace. Heat reduce it at 400°C for 10 h at a high purity hydrogen flow rate of 100 ml / min. After cooling in the furnace, a porous p-Ge material can be obtained.
[0094] S2, add 0.2g of p-Ge to a mixed solution of 80ml of anhydrous ethanol and 20ml of deionized water, stir and ultrasonicate at an ultrasonic power of 200W for 1h to make the mixed solution uniform. Then add 0.02g of hexadecyltrimethylammonium bromide and 0.25ml of tetraethyl orthosilicate, stir for 30min to make it uniform;
[0095] S3, add 2 ml of ammonia water to the above mixed solution until pH = 9 to trigger the hydrolysis of tetraethyl orthosilicate, and stir for 24 hours. After the hydrolysis reaction is completed, centrifuge and wash at 6000 rpm for 5 times with deionized water and anhydrous ethanol, and dry at 80 ° C for 12 hours to obtain p-Ge / SiO 2 -0.25 Composite.
[0096] S4, take 0.3g of p-Ge / SiO 2 -0.25 composite material and 0.2g chitosan were stirred and ultrasonically dispersed in 8g deionized water, and the water in the suspension was evaporated at 150℃ for 2h, and then calcined at 700℃ in Ar atmosphere for 2h to finally obtain p-Ge / SiO 2 / C composite material. The particle size and pore size data are shown in Table 1, and the element percentages are shown in Table 2.
[0097] Figure 1 p-Ge / SiO 2 XRD diffraction pattern of the / C composite material. Compared with the standard PDF card 04-0545, the characteristic diffraction peak of Ge appears, and an obvious broad peak appears near 22°, which is amorphous SiO 2 and carbon peaks.
[0098] Figure 2 p-Ge / SiO 2 / C composite material. As can be seen from the figure, p-Ge / SiO 2 The pore structure of the / C composite material almost disappeared, and the outer surface was covered with SiO 2 Microspheres and covered with an amorphous carbon layer.
[0099] Step 2: Preparation of button lithium-ion battery
[0100] The active material (p-Ge / SiO2 / C composite material), SuperP and polyacrylic acid (PAA) were dissolved in deionized water at a mass ratio of 6:2:2 and then evenly coated on copper foil (coating amount was 0.8g), dried in a vacuum oven at 120℃ for 12h, and then pressed with a roller press. The electrode sheet was cut into a disc with a diameter of 12mm using a slicer to obtain the electrode disc for testing. The CR2032 button half-cell was assembled in an argon-filled glove box, with a lithium sheet as the counter electrode, a Cellgard 2500 film as the separator, and an electrolyte consisting of 1M LiPF 6 It is mixed in EC / DEC / EMC (1:1:1, vol%) with 5 vol% FEC and 1 vol% VC.
[0101] Figure 3 The button-type lithium-ion battery assembled for this embodiment is 0.5Ag -1 Cycling performance diagram in the current density and voltage range of 0.01 to 2.0 V. p-Ge / SiO 2 The final discharge capacity of the C / C composite material after 150 charge and discharge cycles is 730 mAhg -1 , with the highest residual specific capacity, a capacity retention rate of 78.2% (compared with the 4th cycle), and excellent cycle performance.
[0102] Figure 4 The button-type lithium-ion battery assembled for this embodiment is 1.0Ag -1 The current density and cycle performance in the voltage range of 0.01 to 2.0 V. The final discharge capacity of the material after 150 charge and discharge cycles is 627 mAh g -1 , has the highest residual specific capacity, a capacity retention rate of 69.7% (compared with the 4th cycle), and excellent cycle performance.
[0103] Figure 5 This is a rate performance diagram of the button-type lithium-ion battery assembled in this embodiment at different current densities. It can be seen from the figure that the material -1 The current density is 677 mAh g -1 After cycling at different current densities, when the current density is finally maintained at 1.0A g -1 After 120 cycles, the final discharge capacity is 701 mAh g -1 , the capacity retention rate is as high as 85.4% (compared with the 31st cycle), showing the best rate performance.
[0104] Figure 6The electrochemical impedance spectroscopy (EIS) of the button-type lithium-ion battery assembled for this embodiment was tested in the range of 1 MHz to 0.1 Hz. The charge transfer impedance (Rct value) of the material was about 17Ω, which had the lowest impedance and showed the best conductivity.
[0105] Embodiment 6:
[0106] Step 1: Preparation of p-Ge / C composite materials
[0107] S1. Spread a 2 mm thick layer of germanium dioxide powder in an alumina porcelain boat and place it in a tube furnace. Heat reduce it at 400°C for 10 h at a high purity hydrogen flow rate of 100 ml / min. After cooling in the furnace, a porous p-Ge material can be obtained.
[0108] S2, 0.3g of p-Ge material and 0.2g of chitosan were stirred and ultrasonically dispersed in 8g of deionized water, the water in the suspension was evaporated at 150°C for 2h, and then calcined at 700°C in an Ar atmosphere for 2h to finally obtain a p-Ge / C composite material. The particle size and pore size data are shown in Table 1, and the element percentage is shown in Table 2.
[0109] Figure 1 This is the XRD diffraction pattern of the p-Ge / C composite material. Compared with the standard PDF card 04-0545, the characteristic diffraction peak of Ge appears. The diffraction peak of carbon is not observed because the carbon content is not high and it is amorphous.
[0110] Figure 2 This is a SEM image of the p-Ge / C composite material. As can be seen from the image, the pore structure of the p-Ge / C composite material is not obvious, and the outer surface is covered by an amorphous carbon layer.
[0111] Step 2: Preparation of button lithium-ion battery
[0112] The active material (p-Ge / C composite material), SuperP and polyacrylic acid (PAA) were dissolved in deionized water at a mass ratio of 6:2:2 and evenly coated on copper foil (coating amount was 0.8 g), dried in a vacuum oven at 120°C for 12 hours, and then pressed with a roller press. The electrode sheet was cut into a 12 mm diameter disc using a slicer to obtain the electrode disc for testing. The CR2032 button half-cell was assembled in an argon-filled glove box, with a lithium sheet as the counter electrode, a Cellgard2500 film as the separator, and an electrolyte consisting of 1M LiPF 6 It is mixed in EC / DEC / EMC (1:1:1, vol%) with 5 vol% FEC and 1 vol% VC.
[0113] Figure 3 The button-type lithium-ion battery assembled for this embodiment is 0.5Ag-1 Cycling performance diagram in the current density and voltage range of 0.01 to 2.0 V. The capacity of the p-Ge / C composite material dropped sharply after 150 charge and discharge cycles, and the final discharge specific capacity remained 430 mAh g -1 The capacity retention rate is 31.2% (compared with the 4th cycle), and the cycle stability is poor.
[0114] Figure 4 The button-type lithium-ion battery assembled for this embodiment is 1.0Ag -1 Cyclic performance diagram in the current density and voltage range of 0.01 to 2.0 V. The capacity of the material dropped sharply after 150 charge and discharge cycles, and the final discharge capacity was only 334 mAh g -1 , the capacity retention rate is only 23.4% (compared with the 4th cycle), and the cycle stability under high current is poor.
[0115] Figure 5 This is the rate performance diagram of the button-type lithium-ion battery assembled in this embodiment at different current densities. It can be seen from the figure that after the material is cycled at different current densities, when the current density is finally maintained at 1.0Ag -1 After 120 cycles, the final discharge capacity is only 480 mAh g -1 , the capacity retention rate is only 36.6% (compared with the 31st cycle), showing poor rate performance.
[0116] Figure 6 The electrochemical impedance spectroscopy (EIS) of the button-type lithium-ion battery assembled in this embodiment was tested in the range of 1 MHz to 0.1 Hz. The charge transfer impedance (Rct value) of the material was about 23Ω.
[0117] The p-Ge, p-Ge / C, p-Ge / SiO prepared in Examples 1, 2, 3, 4, 5 and 6 of the present invention 2 and p-Ge / SiO 2 The average particle size and pore size data of the / C composite material are shown in Table 1:
[0118] Table 1 Average particle size and pore size data of various examples
[0119]
[0120] The p-Ge, p-Ge / C, p-Ge / SiO prepared in Examples 1, 2, 3, 4, 5 and 6 of the present invention 2 and p-Ge / SiO 2 The percentage of each element in the / C composite material is shown in Table 2:
[0121] Table 2 Summary of element percentages of materials in various embodiments
[0122]
[0123] The above-described embodiments are only preferred solutions of the present invention and are not intended to limit the present invention in any form. There are other variations and modifications without exceeding the technical solutions described in the claims.
Claims
1. A method for preparing a high-performance germanium-based negative electrode material of carbon-coated and silicon dioxide-embedded porous germanium, characterized in that: The method comprises the following steps: S1, subjecting germanium dioxide powder to a low-temperature thermal reduction reaction in a hydrogen atmosphere to obtain a porous germanium material p-Ge material; S2, adding p-Ge to a mixed solution of anhydrous ethanol and deionized water, then adding a surfactant and tetraethyl orthosilicate and stirring evenly, and reacting under alkaline conditions; S3. Carbon-coating the above reaction product to obtain a high-performance germanium-based negative electrode material.
2. The method for preparing a high-performance germanium-based negative electrode material of carbon-coated and silicon dioxide-embedded porous germanium according to claim 1, characterized in that: The particle size of the germanium dioxide powder in step S1 is 3 to 30 microns.
3. The method for preparing a high-performance germanium-based negative electrode material of carbon-coated and silicon dioxide-embedded porous germanium according to claim 1, characterized in that: In step S1, the flow rate of hydrogen atmosphere should be maintained at 50-200 mL / min.
4. The method for preparing a high-performance germanium-based negative electrode material of carbon-coated and silicon dioxide-embedded porous germanium according to claim 1, characterized in that: The thermal reduction condition in step S1 is thermal reduction at 400° C. for more than 8 hours.
5. The method for preparing a high-performance germanium-based negative electrode material of carbon-coated and silicon dioxide-embedded porous germanium according to claim 1, characterized in that: The volume ratio of deionized water to anhydrous ethanol in the mixed solution in step S2 should be 1:(1-5).
6. The method for preparing a high-performance germanium-based negative electrode material of carbon-coated and silicon dioxide-embedded porous germanium according to claim 1, characterized in that: In step S2, the mass ratio of p-Ge to surfactant should be 20:(0.1-2), and the volume ratio of deionized water to tetraethyl orthosilicate should be 20:(0.1-2).
7. The method for preparing a high-performance germanium-based negative electrode material of carbon-coated and silicon dioxide-embedded porous germanium according to claim 1, characterized in that: In step S2, the alkaline condition is a pH not less than 8, and the reaction time is not less than 18 hours.
8. The method for preparing a high-performance germanium-based negative electrode material of carbon-coated and silicon dioxide-embedded porous germanium according to claim 1, characterized in that: The carbon coating step in step S3 is specifically as follows: dispersing the reaction product and the carbon material into deionized water, evaporating the water in the suspension, and then calcining in an inert atmosphere at 600-900° C. for 2 hours.
9. A high performance germanium-based negative electrode material comprising carbon-coated and silicon dioxide-embedded porous germanium prepared by the preparation method according to any one of claims 1 to 8.
10. Application of the high-performance germanium-based negative electrode material of carbon coating and silicon dioxide embedded in porous germanium as claimed in claim 9 in the field of negative electrode materials for lithium-ion batteries.
Citation Information
Patent Citations
Preparation method of germanium nano-particle / multi-layer graphite compound-based high-performance anode material for lithium-ion battery
CN105529442A
Lithium ion battery porous germanium anode material and preparation method and application thereof
CN106159247A
Nitrogen-doped carbon coating germanium composite lithium battery negative electrode material and preparation method and application thereof
CN106169572A
Preparation method and application of porous silicon carbon or germanium carbon material
CN113809314A
Negative electrode material and preparation method thereof, negative electrode plate and lithium ion battery
CN116093287A
Cited By
Co-doped GeO2 lithium ion battery negative electrode material as well as preparation method and application thereof
CN122348197A
A Co-doped GeO2 lithium-ion battery anode material, its preparation method and application
CN122348197B